REIKI - A NEW PARADIGM OF EXISTENCE (Heritage, 2022)
Reiki represents a self-help technique that explains how we can balance our own inner energy in relation to the outer energy of the universe around us, because it is the basis of peace and tranquility that bring positive realization to life.Reiki is a natural self-help technique where a person helps himself using his own energy and the energy that surrounds him. This phenomenon has been understood and accepted since time immemorial by man in all traditions and cultures where man has dealt with his personal healing, philosophy of life and his own place in nature.When Reiki originated cannot be claimed with certainty. The first traces of this technique are recorded in ancient Lotus Sutras written more than 5,000 years ago.After centuries of oblivion, the first to restore this philosophy was a Japanese, Mikao Usui. This high-frequency phenomenon was ascertained in the nineteenth century in Japan.
Keywords: reiki, energy, health, healing, health-attainment